2003
DOI: 10.1046/j.1464-410x.2003.04104.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB nuclear localization and its prognostic significance in prostate cancer

Abstract: RESULTSThe NF-k B subcellular localization was initially assessed in 45 specimens; in these samples a nuclear localization of NF-k B was specific to cancer tissues, but did not correlate with the Gleason score ( P = 0.089). NF-k B was then assessed as a prognostic marker to complement Gleason score in predicting cancer progression. Tumour tissues from 30 men with a known clinical outcome were included; 10 of 17 patients who had a poor outcome were positive for NF-k B nuclear staining, whereas only two of 13 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
95
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 33 publications
16
95
0
1
Order By: Relevance
“…In another study, nuclear NF-kB was found in 40% of prostate tumours in 40 specimens assayed (Lessard et al, 2003). As in the current study, nuclear NF-kB did not significantly correlate with Gleason score.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In another study, nuclear NF-kB was found in 40% of prostate tumours in 40 specimens assayed (Lessard et al, 2003). As in the current study, nuclear NF-kB did not significantly correlate with Gleason score.…”
Section: Discussionsupporting
confidence: 65%
“…As in the current study, nuclear NF-kB did not significantly correlate with Gleason score. In a highly selected series of 30 patients, nuclear localisation was significantly associated with the prognostic groups (Lessard et al, 2003). Multivariate analysis was not reported in that study.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…NF-kB can regulate of proliferation and apoptosis in a variety of cells including prostate cancer cells (Paule et al, 2007;Karin, 2009;Sambantham et al, 2013). Moreover, NF-kB is commonly activated in invasive prostate cancer (Lessard et al, 2003;Ross et al, 2004;Shukla et al, 2004) and of NF-kB-responsive genes are commonly associated with prostate cancer progression (Shukla et al, 2004). Thus, NF-kB provides an attractive therapeutic target for the treatment of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%